Impact of the coronavirus disease 2019 (COVID-19) pandemic on antimicrobial stewardship programs in Colorado hospitals - Caleb L. Matteson; Christopher A. Czaja; Matthew P. Kronman; Sonja Ziniel; Sarah K. Parker; Daniel S. Dodson (Cambridge University Press, 2022)
Using a mixed-methods approach, we assessed the effect of the coronavirus disease 2019 (COVID-19) pandemic on antimicrobial stewardship programs (ASPs) in Colorado hospitals. ASP leaders reported decreased time and resources, reduced rigor of stewardship interventions, inability to complete new initiatives, and interpersonal challenges. Stewardship activities may be threatened during times of acute resource pressure.